Water Use Patterns of Four Tropical Bamboo Species Assessed with Sap Flux Measurements - Mei, Tingting; Fang, Dongming; Röll, Alexander; Niu, Furong; Hendrayanto,; Hölscher, Dirk (Frontiers in Plant Science, 2016)
Bamboos are grasses (Poaceae) that are widespread in tropical and subtropical regions. We aimed at exploring water use patterns of four tropical bamboo species (Bambusa vulgaris, Dendrocalamus asper, Gigantochloa atroviolacea and Gigantochloa apus) with sap flux measurement techniques. Our approach included three experimental steps: (1) a pot experiment with a comparison of thermal dissipation probes, the stem heat balance method and gravimetric readings using potted B. vulgaris culms, (2) an in situ calibration of thermal dissipation probes with the stem heat balance method for the four bamboo species, and (3) field monitoring of sap flux of the four bamboo species along with three tropical tree species (Gmelina arborea, Shorea leprosula and Hevea brasiliensis) during a dry and a wet period. In the pot experiment, it was confirmed that the stem heat balance method is well suited for bamboos but that thermal dissipation probes need to be calibrated. In situ, species-specific parameters for such calibration formulas were derived. During field monitoring we found that some bamboo species reached high maximum sap flux densities. Across bamboo species, maximal sap flux density increased with decreasing culm diameter. In the diurnal course, sap flux densities in bamboos peaked much earlier than radiation and vapor pressure deficit (VPD), and also much earlier than sap flux densities in trees. There was a pronounced hysteresis between sap flux density and VPD in bamboos, which was less pronounced in trees. Three of the four bamboo species showed reduced sap flux densities at high VPD values during the dry period, which was associated with a decrease in soil moisture content. Possible roles of internal water storage, root pressure and stomatal sensitivity are discussed.